Effects of Nitrogen Fertilizer Application on Growth, Vegetation Indices, and Ammonia Volatilization in Korean Radish (Raphanus sativus L.) - TaeSeon Eom; TaeWan Kim; SungYung Yoo (Nitrogen)
Nitrogen use efficiency (NUE) in plants is reduced when treated with excess nitrogen fertilizer. Our study aimed to investigate the impact of varied concentrations of urea on the growth responses, vegetation indices, and ammonia volatilization in radishes. The experiment was conducted across four concentrations of urea (nitrogen source): 0 N (0 kg urea ha−1), 0.5 N (117 kg urea ha−1), 1 N (234 kg urea ha−1), and 2 N (468 kg urea ha−1). Compost was applied as a basal fertilizer in all treatments. Aboveground and belowground biomass were evaluated to measure growth response. The dynamic chamber method was used to collect ammonia volatilized from the cultivation area, and the vegetation index analysis was conducted to assess the effects of nitrogen fertilizer treatment. Our study results suggest there are no significant differences in the yield of radishes between the recommended nitrogen fertilization level (1 N) and half the recommended level in the Republic of Korea (0.5 N). Ammonia volatilization was significantly the lowest in the 0.5 N nitrogen fertilizer treatment among all treatments. Except for a few specific indices, there were no significant differences observed in most analyzed vegetation indices. Based on the specific environmental and soil conditions examined in this study, our results indicate that nitrogen input in radish cultivation in the Republic of Korea could be reduced without significant yield penalties, offering potential benefits in terms of reduced production costs and environmental impact. Nevertheless, to establish optimized fertilizer recommendations, further studies across diverse environmental conditions and cultivation practices, including planting timing, are essential.